(untitled) (Research, Society and Development, 2022)
The purpose of this study was to evaluate the level of physical fitness of students from the Escola Estadual Venceslau Brás (Venceslau Brás State School) in the city of Jaíba - MG, which are teenagers with ages between 12 and 14 years old, of both sexes, who are part of the 7th to 9th grade classes of the Fundamental II Teaching, evaluated in a general way (General Sample) and by division into the group Participant in the Handball Project (PH) and the group Not Participant in the Handball Project (NPH). The study is characterized as a field study, with cross-sectional, descriptive, comparative, quantitative duration. It was carried out with 168 students from Venceslau Brás State School (EVB) in the city of Jaíba - MG, who had ages between 12 and 14 years old from the 7th to the 9th grade of Elementary School II. The main results showed that the students aged between 12 and 14 years old, enrolled from 7th to 9th grade in EVB, have positive indexes (Healthy Zone) about the ApFRS of the physical valences that contemplate this research (BMI, FLEX and RML), with an average higher than 75%, in this classification. In the ApFRD, the performances were more often classified as Good and Very Good in the FMMII, FMSS and AGIL, both in the GA and in its division into PH and NPH, but there is a decrease in the classification, to Weak in the VEL. In view of these results, this work presented new evidences about ApFRS and ApFRD of adolescents with the handball modality. Keywords: Physical fitness; Handball; Health-related physical fitness; Performance-related physical fitness.